2021
DOI: 10.1108/lodj-03-2020-0112
|View full text |Cite
|
Sign up to set email alerts
|

A two-nation investigation of leadership self-perceptions and motivation to lead in early adulthood: the moderating role of gender and socio-economic status

Abstract: PurposeDrawing on the social-cognitive and motivational literature of leadership, the present study examines the influence of young adults' self-perceptions of leadership on their leadership self-efficacy (LSE) and motivation to lead (MTL) in their future career. The authors further examine gender and socio-economic status (SES) as important moderators of the proposed relationships.Design/methodology/approachThe present investigation consists of a two-study research design, based on data collected from young a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 93 publications
0
9
1
Order By: Relevance
“…Thus, we propose that exposure to adverse socioeconomic conditions during adolescence will result indirectly in those young adults being less motivated to become leaders themselves. However, even though some evidence exists of significant zero-order correlations between SES and affective-identity motivation to lead (Hoyland et al. , 2021), we do not predict that SES adversity directly affects affective-identity motivation to lead.…”
Section: Theoretical Backgroundcontrasting
confidence: 98%
See 3 more Smart Citations
“…Thus, we propose that exposure to adverse socioeconomic conditions during adolescence will result indirectly in those young adults being less motivated to become leaders themselves. However, even though some evidence exists of significant zero-order correlations between SES and affective-identity motivation to lead (Hoyland et al. , 2021), we do not predict that SES adversity directly affects affective-identity motivation to lead.…”
Section: Theoretical Backgroundcontrasting
confidence: 98%
“…Some support for this notion derives from Barling and Weatherhead (2016), who showed that the link between personal mastery and leader role occupancy was significantly higher among males than females. In addition, the relationship between leadership self-efficacy and affective-identity motivation to lead was significant for male high school students in the UK, but not for females (Hoyland et al, 2021). Thus, we predict that the relationship between sociometric status and affective-identity motivation to lead will be higher among female compared to male participants, while the corresponding relationship between self-esteem and affective-identity motivation to lead will be higher among male participants.…”
Section: Affectiveidentity Motivation To Leadmentioning
confidence: 75%
See 2 more Smart Citations
“…The actors cannot be seen independently of the context that they participate as well as they cannot be seen independently of the people that relate with (Dimitriadis and Psychogios, 2020 ). For example a recent study found that the perceptions of leadership as well as aspiration for leadership are influenced by both cultural and socioeconomic elements (Hoyland et al, 2021 ). In other words, leadership occurs within the process of relating with each other, aiming in doing things in a non-static, but dynamic and continuously evolving context.…”
Section: Relational Leadership On Boardmentioning
confidence: 99%